Answer:
Step-by-step explanation:im not good at long answers but it should push each other away.
-2 = - x + x^2 -4 => x^2 - x - 4 + 2 = 0
x^2 - x - 2 = 0
a is the coefficient of x^2 => a = 1
b is the coefficient of x => b = - 1
c is the constant term => c = - 2
quadratic equation: [- b +/- √(b^2 - 4ac) ] / 2a =
= { 1 +/- √[ (-1)^2 - 4(1)(-2)] } / (2(1) = { 1 +/- √ (1 + 8) } / 2 = {1 +/- √9} / 2 =
= { 1 +/- 3} / 2
I think it is B because it isn’t a solid line and it’s going up
2/5 is the answer unless your multiplying
3 = -(-y + 6)
First, simplify brackets. / Your problem should look like: 3 = y - 6
Second, add 6 to both sides. / Your problem should look like: 3 + 6 = y
Third, simplify 3 + 6 to 9. / Your problem should look like: 9 = y
Fourth, switch sides. / Your problem should look like: y = 9
The answer is D) 9.